Transmission of HIV Drug Resistance and the Predicted Effect on Current First-line Regimens in Europe. - Hofstra, L Marije; Sauvageot, Nicolas; Albert, Jan; Alexiev, Ivailo; Garcia, Federico; Struck, Daniel; Van de Vijver, David A M C; Åsjö, Birgitta; Beshkov, Danail; Coughlan, Suzie; Descamps, Diane; Griskevicius, Algirdas; et al. (Clin Infect Dis, 2016)
BACKGROUND: Numerous studies have shown that baseline drug resistance patterns may influence the outcome of antiretroviral therapy. Therefore, guidelines recommend drug resistance testing to guide the choice of initial regimen. In addition to optimizing individual patient management, these baseline resistance data enable transmitted drug resistance (TDR) to be surveyed for public health purposes. The SPREAD program systematically collects data to gain insight into TDR occurring in Europe since 2001. METHODS: Demographic, clinical, and virological data from 4140 antiretroviral-naive human immunodeficiency virus (HIV)-infected individuals from 26 countries who were newly diagnosed between 2008 and 2010 were analyzed. Evidence of TDR was defined using the WHO list for surveillance of drug resistance mutations. Prevalence of TDR was assessed over time by comparing the results to SPREAD data from 2002 to 2007. Baseline susceptibility to antiretroviral drugs was predicted using the Stanford HIVdb program version 7.0. RESULTS: The overall prevalence of TDR did not change significantly over time and was 8.3% (95% confidence interval, 7.2%-9.5%) in 2008-2010. The most frequent indicators of TDR were nucleoside reverse transcriptase inhibitor (NRTI) mutations (4.5%), followed by nonnucleoside reverse transcriptase inhibitor (NNRTI) mutations (2.9%) and protease inhibitor mutations (2.0%). Baseline mutations were most predictive of reduced susceptibility to initial NNRTI-based regimens: 4.5% and 6.5% of patient isolates were predicted to have resistance to regimens containing efavirenz or rilpivirine, respectively, independent of current NRTI backbones. CONCLUSIONS: Although TDR was highest for NRTIs, the impact of baseline drug resistance patterns on susceptibility was largest for NNRTIs. The prevalence of TDR assessed by epidemiological surveys does not clearly indicate to what degree susceptibility to different drug classes is affected.
Keywords: Adult; Anti-HIV Agents; Drug Resistance, Viral; Europe; Female; HIV Infections; HIV Protease Inhibitors; HIV-1; Humans; Male; Microbial Sensitivity Tests; Middle Aged; Mutation; Prevalence; Reverse Transcriptase Inhibitors